Communication to Political Education: How Instagram Transforms Public Knowledge in the Digital Era - Rizal Fahmi Muhammad (Bulletin of Islamic Research, 2023)
Technology continues to develop and affect several fields, including politics. Political education usually only obtained in formal education such as schools and universities has shifted to social media. The purpose of this research is to explain how social media can increase public knowledge about politics and social media in the digital era has changed its function, which used to be only to communicate with others but now social media can be used for political education. Agenda setting theory is used to find out how Instagram social media on pinterpolitik and totalpolitik accounts educate the public. Methodology This article uses a qualitative description approach with a literature study. Primary data comes from recent books and journals on political education, political communication, and social media. Secondary data comes from observation, the socialblade.com website from July 2019 to January 2024, and social media information. This study's result is that pinterpolitik accounts educate with content that contains interesting infographics, interesting titles, trusted sources, interesting visuals, current political issues, and short, concise, and clear content. Meanwhile, the totalpolitikcom account is slightly different from the pinterpolitik account on Instagram account, the difference can be seen in the uploaded content where they use images and provide captions on the content below the image, and per content uploaded on Instagram, totalpolitikcom uses an average of 2 slides of content. In the future, research on political education through social media can be carried out with a more in-depth analysis and the object of research is not only two accounts, this is because of comparison with other social media accounts that discuss political education.